2021
DOI: 10.1002/rth2.12566
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with pulmonary embolism treated with edoxaban versus warfarin

Abstract: Background Long‐term sequelae of acute pulmonary embolism (PE) include decreased quality of life (QoL). Evidence suggests that adequacy of initial anticoagulant treatment in the acute phase of venous thrombosis has a key impact on late postthrombotic complications. We hypothesize that patients with acute PE treated with edoxaban for acute PE experience have improved QoL compared to those treated with warfarin. Methods Patients with PE who participated in the Hokusai‐VTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In 2021, Bavalia et al published the quality of life results of 251 patients treated with edoxaban or warfarin for PE in the Hokusai-VTE trial at 7 years after randomization. In this single visit study, the authors observed no difference in QoL between the two groups based on the 36-item Short Form Health Questionnaire (SF-36) and Pulmonary Embolism Quality of Life Questionnaire (PEMB-QOL) scores [74].…”
Section: Treatment Of Vtementioning
confidence: 70%
“…In 2021, Bavalia et al published the quality of life results of 251 patients treated with edoxaban or warfarin for PE in the Hokusai-VTE trial at 7 years after randomization. In this single visit study, the authors observed no difference in QoL between the two groups based on the 36-item Short Form Health Questionnaire (SF-36) and Pulmonary Embolism Quality of Life Questionnaire (PEMB-QOL) scores [74].…”
Section: Treatment Of Vtementioning
confidence: 70%
“…We previously reported the methods and findings of the Hokusai post‐PE study. 38 In short, in 2016, we approached 78 study centers, based on the number of patients included in the original Hokusai‐VTE trial (>10 patients) and language, and located in Austria, Australia, Belgium, Canada, Denmark, France, Germany, Italy, the Netherlands, New Zealand, Norway, United Kingdom, and United States of America to participate in the Hokusai post‐VTE study. Patients were eligible for the current follow‐up study if they were recruited in one of these study centers and treated for DVT (with or without PE) as their index event for participation in the Hokusai‐VTE trial.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analysis was conducted according to the statistical analysis plan for the Hokusai post‐VTE studies and therefore similar to the Hokusai post‐PE study 38 . Differences in baseline characteristics between both groups were evaluated by means of the 2‐sample t tests for normally distributed variables and the Mann–Whitney test for skewed distributions; χ 2 tests were applied for categorical data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation